The Sex warriors and the Samurai - Deocampo, Nick (Center for New Cinema, 1995)
A candid story about a Filipino transgender who works in Japan's entertainment center in order to support his family. In the daytime, Joan attends to his daily training to prepare him for work as entertainer in Japan. At night, he works as one of the female impersonators in Manila's gay bars. All these to feed a family of eighteen. Although it will be Joan's fourth trip to Japan, he still finds it hard to make as much money to make their lives better. Meeting other gay entertainers in the bar where he works, they talk about the difficulties Filipino entertainers experience while working in Japan. The situation is no different though from the life lived by Semeon like Joan in the Philippines who was once caught in a drug bust operation and sent to jail. Threats and difficulties seem to hound these sex warriors wherever they go. The film climaxes with his father's release from jail and he gets to meet his family. The scene where Joan bonds with his father is filled with pathos and affection, offering a precious glimpse into a Filipino family and how it relates with its gay son. Joan's story rises above mere personal triumph as it reflects the geo-political relations governing Japan and the Philippines, two countries historically linked with a brutal war and currently meshed by a global economy.